Adsorption of Nickel Ions From Aqueaus Solution Using Natural Clay - Al-atabe, Mohammed Jaafar Ali; Hussein, Ahmed Alaa (Al-Nahrain Journal for Engineering Sciences, 2018)
The adsorption characteristics of Nickel (II) onto Iraqi Bentonite clay from aqueous solution have been investigated with respect to changes in pH of solution, adsorbent dosage, contact time and temperature of the solution. The maximum removal efficiency of Nickel (II) ions is 96% at pH=6.5 and exposure to 100 g/L adsorbent. For the adsorption of Nickel (II) ions, the Freundlich isotherm model fitted the equilibrium data better than the Langmuir isotherm model. Experimental data are also evaluated in terms of kinetic characteristics of adsorption and it was found that the adsorption process for Ni+2 ions follows well pseudo-second-order kinetics. Thermodynamic functions, the change of free energy (?G°), enthalpy (?H°) and entropy (?S°) of adsorption are also calculated for Nickel (II) ions. The results show that the adsorption of the Nickel (II) ions on Iraqi Bentonite is feasible and exothermic at (20-50) °C.